Solution‐Processable Carbon Nitride Polymers for Photoelectrochemical Applications. Issue 12 (26th July 2019) - Karjule, Neeta; Phatake, Ravindra; Volokh, Michael; Hod, Idan; Shalom, Menny
Abstract: A general and straightforward synthesis of a series of solution‐processable carbon nitride polymers is described with excellent and tunable optical and electronic properties. The high dispersibility of carbon nitride polymers functionalized with polycyclic aromatic hydrocarbons (PAH‐CNs) in common solvents permits their facile processing into thin films utilizing routine methods such as spin‐coating and drop‐casting. Moreover, altering the PAH group within the CN scaffold enables great tunability of their optical and electronic properties as well as a range of functionalities. This is illustrated by a variety of photoelectrochemical properties, electropolymerization ability, and photoswitching properties for the different PAH‐CNs. The easy processing and tunable properties allow the construction of advanced electronic structures, such as a heterojunction, which significantly improves the photoelectrochemical performance. The versatility of this solution‐processable platform holds promise for the applicability of CNs in new photoelectronic devices. Abstract : Polycyclic aromatic hydrocarbon‐modified carbon nitrides (PAH‐CNs) are synthesized and investigated for photoelectrochemical, photoswitching and electropolymerization studies. These new CN materials have excellent dispersibility which allows easy deposition on various substrates using common thin film fabrication techniques such as drop‐casting and spin‐coating under mild conditions.